Review of The Metaphysics of Science and Aim-Oriented Empiricism, by Nicholas Maxwell - Damian Fernandez Beanato (Principia: An International Journal of Epistemology)
This is a review of the book Maxwell, N. 2019. The Metaphysics of Science and Aim-Oriented Empiricism. Springer.